2016
DOI: 10.1007/s11011-016-9882-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hyperprolactinaemia reduces total cholesterol and LDL in patients with prolactinomas

Abstract: Previous studies suggest that hyperprolactinaemia might have adverse effects on lipid and glucose metabolism. We therefore aimed to evaluate whether dopamine agonist treatment with cabergoline has significant effects on blood lipids, fasting glucose and HbA1c levels in patients with micro- or macroprolactinoma. In this retrospective observational study the main outcome measures are changes in parameters of glucose and lipid metabolism compared at hyperprolactinaemia and after achievement of normoprolactinaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…DAs reduce triglycerides, fasting glucose, and LDL cholesterol in individuals with prolactinomas [127]. In contrast, in another study on prolactinoma patients offered DA demonstrated no change in fasting glucose, although significant decrease of LDL and total cholesterol were observed [128]. A report of 20 premenopausal women with prolactinoma described significant decreases in BMI, total cholesterol, and LDL following treatment with DA [129].…”
Section: Metabolic Riskmentioning
confidence: 94%
“…DAs reduce triglycerides, fasting glucose, and LDL cholesterol in individuals with prolactinomas [127]. In contrast, in another study on prolactinoma patients offered DA demonstrated no change in fasting glucose, although significant decrease of LDL and total cholesterol were observed [128]. A report of 20 premenopausal women with prolactinoma described significant decreases in BMI, total cholesterol, and LDL following treatment with DA [129].…”
Section: Metabolic Riskmentioning
confidence: 94%
“…Focus on increased cardiovascular risk in males with hyperprolactinemia is warranted. density lipoprotein cholesterol (LDL-C) [9][10][11][12][13]. It has been suggested that hyperprolactinemia induces hyperphagia leading to obesity [14,15], and that prolactin directly regulates enzymes involved in glucose and lipid metabolism in target organs [16].…”
Section: Hyperprolactinemia and The Association With All-cause Mortalmentioning
confidence: 99%
“…12 Both OPH and ScH are associated with varying degrees of hyperprolactinaemia, the correction of which is associated with reduction in cholesterol levels, insulin resistance and improvement in glycaemia. [13][14][15][16] This underpins the use of dopamine agonist therapy in metabolic syndrome/type 2 diabetes. 15,16 Studies have consistently shown that restoration of euthyroidism with levothyroxine supplementation is associated with reduction in levels of triglycerides, LDL-C and apo-B levels.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] This underpins the use of dopamine agonist therapy in metabolic syndrome/type 2 diabetes. 15,16 Studies have consistently shown that restoration of euthyroidism with levothyroxine supplementation is associated with reduction in levels of triglycerides, LDL-C and apo-B levels. 17 Levothyroxine therapy has no impact on apo-A1 levels.…”
Section: Discussionmentioning
confidence: 99%